Avaliação do desenvolvimento da Salicornia neei Lag. consorciada com palma miúda, sorgo-do-sudão e milheto. - Barreto, Gilvanete Cabral de Mendonça (2020)
Brazil's Northeast region covers 18.2% of the Brazilian territory, and 62% is in the drought polygon. The semi-arid region has its climate, soil and hydrological giving the region restrictions for regular use of water supplies, requiring a diversity drought resistant vegetation and soil salinization; due to this feature, it is necessary the cultivation of halophytes and grasses that support live in soils high in salinity because they absorb the salt contributing to the recovery of soils and serving of food and feed. It is irrigated with desalination of waste, minimizing environmental impacts. The search for low-cost alternatives that suit the particular environment is continuous and requires efficient alternatives that can bring benefits to the local farmer. This work evaluated the effect of the consortium with the Salicornia neei, the Nopalea cochenillifera (small palm), the Sorghum sudanense (sorghum sudan), the Pennisetum glaucum (millet) submitted to irrigation with desalinator. The experiment were carried out in greenhouse in the Agronomic Institute of Pernambuco (IPA), Recife, Pernambuco. The experimental design was randomized block. The treatments consisted of individual planting of Salicornia neei and Small palm, Salicornia and Sorghum, Salicornia and Millet, individually and in a consortium, in three soil types (clay, sandy and medium) using two types of irrigation (water and reject desalinator) with a randomized block design, with three repetitions. After 180 days, it was observed that the consorciated Salicornia neei and Palm (Nopalea cochenillifera) presented a better production of green (1,216.74 kg/ha) and dry (243.35 kg/ha) matter, when irrigated with desalinator reject and cultivated in the soil with sandy texture. The planting of only Sorghum sudanense presented a better production of green (400 kg/ha) and dry (80 kg/ha) matter, when irrigated with desalinator reject and cultivated in the soil with clayey texture. Salicornia neei in consortium with Sorghum sudanense showed better absorption of sodium (5.91%), potassium (2.53%), calcium (1.77%) and magnesium (3.29%) in the soil with clayey texture and irrigated with desalinator reject. The Salicornia neei and Pennisetum glaucum intercropping, in soil with clayey texture, presented better results for total fiber (25.05%), total nitrogen (1.20%) and total protein (7.54%) when irrigated with water; and higher sodium(1.79%) absorption when irrigated with desalinator reject.